PROVIDING ENGLISH LANGUAGE INPUT: DECREASING STUDENTS’ ANXIETY IN READING COMPREHENSION PERFORMANCE - Elva Yohana (Jurnal Bahasa Lingua Scientia, 2016)
The primary condition for successful in second or foreign language learning is providing an adequate environment. It is as a medium of increasing the students’ language exposure in order to be able to success in acquiring second or foreign language profciency. This study was designed to propose the adequate English language input that can decrease the students’ anxiety in reading comprehension performance. Of the four skills, somehow reading can be regarded as especially important because reading is assumed to be the central means for learning new information. Some students, however, still encounter many problems in reading. It is because of their anxiety when they are reading. Providing and creating an interesting-contextual reading material and gratifed teachers can make out this problem which occurs mostly in Indonesian’s classrooms. It revealed that the younger learners of English there do not received adequate amount of the target language input in their learning of English. Hence, it suggested the adoption of extensive reading programs as the most effective means in the creation of an input-rich environment in EFL learning contexts. Besides they also give suggestion to book writers and publisher to provide myriad books that appropriate and readable for their students.